Referring Survivors of Endometrial Cancer and Complex Atypical Hyperplasia to Bariatric Specialists: A Prospective Cohort Study - JERNIGAN, Amelia M. (Am J Obstet Gynecol, 2015)
OBJECTIVE(S): To describe the acceptability of bariatric referrals when offered by gynecologic oncologists to women with a history of complex atypical hyperplasia or early stage endometrial cancer and to detail compliance with referrals and weight loss attempts initiated three months after the referral. STUDY DESIGN: Obese women with complex atypical hyperplasia or early stage endometrial cancer were approached for inclusion in this prospective cohort study. Those not in the care of a bariatric specialist were offered a medical referral with or without a surgical referral. A survey was administered at inclusion and after three months. RESULTS: Of 121 women approached, 106 were consented. Women reported that it was acceptable for their gynecologic oncologist to discuss weight loss (91.09%) and that a 10% loss of body weight would be beneficial (86.14%). Six women were already in the care of a bariatric specialist. Of the remaining 100, 43 accepted a referral: 35 of 100 medical and 8 of 66 surgical referrals offered. At three months, 17 women complied with a referral (16 medical and 1 surgical) and 59 had initiated any weight loss attempt. On multivariate analysis, a higher initial weight (p=0.0403), Charlson Comorbidity Index ≥ 5 (p=0.0278) and shorter time from surgery to bariatric referral (p=0.0338) predicted acceptance of a referral. CONCLUSION(S): Weight loss counseling is well received by these women. After being offered bariatric referral, only 17% comply, but most (59%) subsequently initiate a weight loss attempt. Referrals should be offered early in the course of cancer care to maximize acceptance.